Influence of Wing Dam Notching on Aquatic Macroinvertebrates in Pool 13, Upper Mississippi River : The Prenotching Study - Hall, Thomas J. (University of Wisconsin-Stevens Point, College of Natural Resources, 1980)
Benthic and colonizing macroinvertebrates and physicochemical characteristics were studied at six wing dams and an adjacent side channel in Pool 13 of the Upper Mississippi River in June, August, September through October 1978, and June 1979 in the prenotching phase of a project to determine the effects of wing dam notching on aquatic macroinvertebrates. Three wing dams were notched in May through June 1979. Water temperature and dissolved oxygen concentration were uniform with depth in each sampling period but varied among periods. Current velocity varied with sampling period because staff gauge, i.e. discharge, varied with time. Current velocity decreased with depth. The substrate was mainly medium sand because bottom current velocities ranged from 22 to 43 cm/s during 1978, Fifty-six taxa of macroinvertebrates were collected with a Ponar grab sampler in 1978, Oligochaeta, the most abundant class, comprised 51% of benthic invertebrate density. Hexagenia bilineata (Say), Hexagenia limbata (Serville), and early instars of Hexagenia spp. made up 64% of the benthic biomass. Hydropsychid caddisflies dominated the macroinvertebrate aufwuchs on basket and multiple-plate samplers, which were placed on wing dams. Basket samplers were colonized by significantly greater macroinvertebrate numbers, biomass, and number of taxa than multiple-plate samplers. Total benthic invertebrate, oligochaete, Hexagenia spp., and chironomid density, and biomass and number of benthic taxa each were positively, significantly related to percent silt-clay in the substrate. All of these macroinvertebrate categories were negatively, significantly related to percent sand in the substrate. Although gravel substrate was rare, the highest benthic invertebrate density, biomass, and number of taxa occurred in gravel. Wing dam 25, on the inside of a river bend in an area of reduced current, had significantly greater benthic density and biomass than for other wing dams because of greater silt-clay deposits there. Wing dam 28 had the lowest benthic density, biomass, and number of taxa and the greatest percentage of sand. Benthic density, biomass, and number of taxa were significantly greater at stations above wing dams than below because percentages of silt-clay were greater above than below. Besides substrate, discharge and time of year in relation to invertebrate life cycles affected benthic invertebrate populations. Benthic invertebrates decreased in August 1978 and June 1979 partly because of peak discharges in the month before the decrease and partly because of insect emergence. The wing dams were islands of rock in a sea of sand. Basket samplers collected 26.5 times more macroinvertebrate numbers and 14.3 times more biomass than the Ponar grab sampler in September 1978. These differences were related to habitat, i.e. basket samplers collected invertebrates from a lotic-erosional habitat, and the Ponar grab sampler sampled a lotic-depositional habitat.